Optimal financial contracting and debt maturity structure under adverse selection - Fernández Ruiz, Jorge (Estudios Económicos de El Colegio de México, 2002)
We analyze a model in which a risk-averse country finances its development project under asymmetric information. Before the project renders its fruits, two types of news will become available, one of which will reduce the asymmetry of information between the country and its investors. We characterize the optimal financial contract both when complete financial contracting is possible and when the country is restricted to using only short-term and long-term debt.